2014
DOI: 10.1111/jsm.12637
|View full text |Cite
|
Sign up to set email alerts
|

Further Definition on the Multiple Partner Choice Arena: A Potential Animal Model for the Study of Premature Ejaculation

Abstract: Introduction The multiple partner choice arena (MPCA) is an experimental setup in which male rats display a significant shortening of ejaculation latency, which is the main characteristic of premature ejaculation (PE) in men. Thus, the MPCA is a potential animal model for PE. Aim In this study, we further analyze whether the features of the MPCA satisfy the validity criteria for it to be considered an animal model as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The fact that this effect was not obtained when we also included males with long ejaculation latencies suggests that tasipimidine affects the ease of achieving ejaculation only in animals ejaculating rapidly. Considering the supposition already mentioned, that such animals represent a good model of premature ejaculation, 42,43 these results…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The fact that this effect was not obtained when we also included males with long ejaculation latencies suggests that tasipimidine affects the ease of achieving ejaculation only in animals ejaculating rapidly. Considering the supposition already mentioned, that such animals represent a good model of premature ejaculation, 42,43 these results…”
Section: Discussionmentioning
confidence: 66%
“…It has repeatedly been suggested that male rats with short ejaculation latencies could be considered a model of premature ejaculation. 43,44 Regardless of the validity of that argument, we decided to analyze the effects of tasipimidine in animals with an ejaculation latency after vehicle below the 75 th percentile. In these animals, there was indeed a treatment effect on the ejaculation 2.…”
Section: Sexual Behaviormentioning
confidence: 99%
“…Additionally, this model may be seen as useful in pharmacological and neurobehavioral experiments to evaluate the potential influence of various agents on sexual parameters, which includes selective serotonin reuptake inhibitors, serotonin-norepinephrine reuptake inhibitors, antipsychotic drugs, other 5-HTr modulators, dopamine receptor agents, autonomic nervous system agents, phosphodiesterase inhibitors, nitrates, other types of endogenic substances, and toxic factors ( Olivier et al, 2006 , 2017 , 2022 ; Lin et al, 2015 ; Sanna et al, 2015 ; Chiang and Park, 2020 ; Esquivel-Franco et al, 2020 ; Kermath et al, 2022 ). Similarly, it could be useful in investigations of emotional responses, in addition to models of erectile dysfunction or premature ejaculation ( Hull et al, 1994 ; Sachs, 2000 ; Waldinger and Olivier, 2005 ; Olayo-Lortia et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we argue that this approach could be applied for more precise determination of specific mechanisms involved in abnormal or disturbed sexual behavior in rats that are translationally related to human health disorders. In particular, translational research in rodent models of sexual behavior has provided important insights into the pathomechanisms and pharmacotherapy of clinical conditions that are described in the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM 5) and in the International Statistical Classification of Diseases and Related Health Problems 10th revision (ICD-10), including premature ejaculation, paraphilias, mood and anxiety disorders as well as neurological and metabolic diseases (McVary et al, 1997;Grønli et al, 2005;Giuliano and Clément, 2006;Hawley et al, 2013;Pfaus et al, 2013;Kang et al, 2014;Olayo-Lortia et al, 2014;Sanna et al, 2014;Faulkner et al, 2015;Babaei-Balderlou and Khazali, 2016;Oosting et al, 2016;Ramírez-Rodríguez et al, 2017;Hernández and Fernández-Guasti, 2018;Novati et al, 2018). In this light, we propose that in various rodent models of human disease states, sexual motivation and performance may be differently affected, which is reflected in distinct changes of specific components of male rat sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: ACTH, adrenocorticotropic hormone; CRH, corticotropin-releasing hormone; EF, ejaculation frequency; HPG, hypothalamic-pituitary-gonadal axis; III, inter-intromission interval; PDE5, phosphodiesterase 5; PVs, precontact vocalizations in the 50-kHz band; SSRI, selective serotonin reuptake inhibitor. References in the table: [1] (Pfaus and Phillips, 1991, Van Furth et al, 1994, Barr et al, 1999; [2] (Bialy et al, 2000); [3] (Pfaus et al, 2013); [4] (Fiorino and Phillips, 1999); [5] (Novati et al, 2018); [6] (Barrot et al, 2005, Miwa et al, 2011; [7] (Pfaus and Phillips, 1991); [8] (Faulkner et al, 2015); [9] (Babaei-Balderlou and Khazali, 2016); [10] (Bialy et al, 2014); [11] (Sadeghzadeh et al, 2018); [12] (McVary et al, 1997); [13] (Hawley et al, 2013, Sanna et al, 2014; [14] (Ramírez-Rodríguez et al, 2017, Hernández andFernández-Guasti, 2018); [15] (Coolen et al, 1997, Pattij et al, 2005a, Clément et al, 2007, Kang et al, 2013, Olayo-Lortia et al, 2014; [16] (Grønli et al, 2005); [17] (de Jong et al, 2005, Hueletl-Soto et al, 2012; [18] (Coolen et al, 1997, Beck and; [19] (Harris and Sachs, 1975, Valcourt and Sachs, 1979, Novati et al...…”
Section: Intromission Ratiomentioning
confidence: 99%